Improving Students' Conceptual Understanding with the 5E Learning Cycle Model in Static Fluid Material - Sarah Lutfiah Ardilla; Sutopo Sutopo; Hari Wisodo; Nur Akhyar Basri; Muhammad Ikhbar Ihsan; Muizzatul Islamiyah (Kasuari: Physics Education Journal (KPEJ), 2026)
Static fluids are a difficult topic, and students must understand many of the concepts involved. Students often misunderstand buoyancy, hydrostatic pressure, and Pascal's law. A learning method that uses the 5E learning cycle model can help overcome these misunderstandings. This method trains students to create and use models, analyze data, think mathematically, design experiments, and provide scientific explanations. Through these learning experiences, students should gain a deep understanding of the main ideas of static fluids. This study aimed to enhance students' conceptual understanding of static fluids using the 5E learning cycle model. The research design was a one-group pretest-posttest study with 29 high school students from Brawijaya Smart School in Malang as the subjects. Conceptual understanding was measured using a test comprising 10 multiple-choice questions. Data analysis was performed using the Wilcoxon test to calculate the n-gain value. The analysis revealed a significant improvement in students' conceptual understanding of static fluids after implementing the 5E learning cycle model. The research yielded an n-gain value of 0.55, which falls within the moderate category. Therefore, it can be concluded that the 5E learning cycle model improves students' conceptual understanding of static fluid material.